Penentuan Nilai Rating Produk Menggunakan Metode Weighted Product (WP) (Studi kasus : Toko Online Rudi Palupuh Cell) - Amalia, Rini; Sagita, Sri Melati; Khotijah, Siti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Rudi Palupuh Cell online shop is a shop that sells its goods online using market media. To increase sales, it is necessary to determine the product rating value to evaluate the products that are most sold and in demand by the public and the weighted product (wp) method can help provide an assessment to determine the rating of products sold at the Rudi Palupuh Cell online shop. When using the weighted product (WP) method, a weight value is assigned to each criterion used, where the criteria used are important criteria in determining the product rating value. The criteria used in this method include rating, number sold, number of views and price. This research aims to provide information about the highest ratings that are most popular with consumers so that it is hoped that it can further increase sales, especially at the Onile Palupuh Cell shop.